School of magical animals 2 : the movie [videorecording (DVD)] - Unterwaldt, Sven; Dydyna, Alexander; Nater, Thorsten; Maier, Emilia; Sichrovsky, Loris; Johna, Lilith; Conrads, Leonard; Pieske, Emilia; Uhl, Nadja; Von Dohnǹyi, Justus; Pinkowski, Heiko; Peschel, Milan (Breaking Glass Pictures, 2024)
"The students of the school of magical animals want to perform a musical for the school's anniversary. Will the rehearsals end in chaos or will the class pull together? And what's up with the strange holes on the school grounds? With the help of their magical animals, the children learn what really matters: teamwork" -- Back of container.